Pediatric drug hypersensitivity: which diagnostic tests? - Saretta, Francesca; Mori, Francesca; Cardinale, Fabio; Liotti, Lucia; Franceschini, Fabrizio; Crisafulli, Giuseppe; Caimmi, Silvia; Bottau, Paolo; Bernardini, Roberto; Caffarelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
Along with the anamnesis and clinical evaluation, diagnostic tests are one of the mainstream key points in the evaluation and management of drug hypersensitivity reactions (DHR). A wide knowledge gap, both in diagnosis and management of pediatric DHR, must be filled.  Only a few published studies evaluated sensitivity and specificity of skin and in vitro tests in children. However, selected case series show that diagnostic work-up for adults could be useful, with some limitations, in pediatric age. Indeed, despite improvement in in vivo and in vitro diagnosis, drug provocation test remains the gold standard in pediatric age, too. Unmet needs in children include multi-centric studies on incidence of DHR, utility and feasibility of in vivo and in vitro diagnostic tests and specifically dedicated guidelines for the diagnosis and management of DHR in children.